Pengaruh Profitabilitas, Ukuran Perusahaan dan Komisaris Independen Terhadap Penghindaran Pajak - Maria Lidwina Sukarta; Harti Budi Yanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to provide empirical evidence of influence of profitability, firm size and independent commissioners on tax avoidance. The population in this study is financial companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The sample selection usedpurposive sampling, resulting in 62 companies that met the criteria. The data used is secondary data and uses multiple linear regression analysis. The data was processed using Eviews 12 software. The results showed that profitability has an effect on tax avoidance. Meanwhile, firm size and independent commissioners did not affect tax avoidance.